The Effect of Professional Burnout on the Performance of Academic Staff in Higher Education in Kosova - Besfort Ahmeti; Valentina Murati; Fisnik Morina (Human Research in Rehabilitation)
This research is focused on the level of burnout among academic staff workers in higher education and aims to examine the effects that this phenomenon causes, as well as whether these people show signs of wear and tear from the many loads they have in their efforts to achieve high performance. The primary data were obtained through a survey with the academic staff using the MBI (Maslach Burnout Inventory) assessment. We reveal that the academic staff show symptoms of burnout at a medium level; most of them are not satisfied with their personal achievement, indicating the effects that burnout has on their performance. We also show that there were no differences or any significant relationship between demographics and burnout levels, except for age. The results of this study reveal that the less experienced staff have more energy in the beginning, then go through struggles until they adapt and are able to reach stability in the years close to retirement. There was also a discrepancy in the means between the factors leading to burnout, but this comes due to mental health at the workplace stigma.